Dispute dissolution through dialogue reflecting historical perspective: a proposed OIC framework - Jasimuddin, Sajjad M.; Almuraqab, Nasser (Frontiers in Political Science, 2025)
The Organization of Islamic Cooperation (OIC) is formed to ensure peace and prosperity in its member countries. The paper intends to highlight the contemporary OIC leaders’ acumen to remove their differences, and thereby resume and maintain political relations among them. Moreover, the paper proposes a framework to ensure strong cooperation in various fields (e.g., political, economic and defense) among the OIC member states to ensure tangible benefits for their people. The current phenomenon is that the opposite sides agree to establish the necessary mechanisms with the encouragement of dialogue between them to minimize their differences. The recent trend is that OIC leaders intend to enhance unity and solidarity through dialogue. Most specifically, the contemporary OIC leaders’ acumen prefer a dialogue-centered approach to conflict prevention and resolution of disputes. The paper articulates a framework taking the three constructs (i.e., political ties, economic cooperation and defense alliance) under three layers among OIC countries. These constructs can be viewed as hierarchy of solidifying the foundation of political ties among the member states by removing their differences through dialogue. The three components of the proposed framework that incorporate the three constructs seems to help to ensuring global peace and prosperity. Additionally, this paper guides to understand the way the second largest international organization (after the UNO) with a membership of 57 states can establish closer ties for betterment of their people.